Formation and ultrahigh mechanical strength of multicomponent Co-based bulk glassy alloys - Fang Wang; Akihisa Inoue; Fanli Kong; Shengli Zhu; Chunxiao Xie; Chengliang Zhao; Walter Jose Botta; Chuntao Chang (Journal of Materials Research and Technology, 2023)
A glassy phase with glass transition (GT) was formed in a wide B content range of 12–31 at% for (Co0.75Cr0.125Mo0.125)100-xBx alloys. The appearance of GT at the low metalloid content of 12%B among Co-, Fe- and Ni-based alloys is the first, in contrast to the absence of GT for (Fe0.75Cr0.125Mo0.125)88B12 and (Ni0.75Cr0.125Mo0.125)88B12 alloys. The Co-based 12%B glassy alloy crystallized through unique three stages, i.e., glass (G) → [G + hcp + fcc] → [G + fcc] → [fcc + M23B6]. The appearance of GT is due to the necessity of long-range rearrangement of constituent elements for the simultaneous precipitation of hcp and fcc phases from glassy phase. The glass transition temperature, crystallization temperature, Vickers hardness (Hv) and Young's modulus for the Co-based glassy alloys increase linearly with increasing B content and reach 904 K, 946 K, 1566 and 188 GPa, respectively, at 31%B. The good bending plasticity is retained up to 29%B. The crystallization of the 27–29%B alloy occurs through G → [G + M23B6] → [M23B6 + M2B] and the ultrahigh Hv above 2000 is attained for the metastable [G + M23B6] phase state. The glassy alloy rod with a diameter of 1 mm was prepared for the 27%B alloy and exhibited ultrahigh yield strength of 4700 MPa, plastic strain of 1% and high oxidation resistance up to about 1200 K. The Co-based bulk glassy alloy with simultaneously high strength, ultrahigh hardness and high oxidation resistance, is promising for the future high hardness and heat-resistance materials.